2022
DOI: 10.1021/acs.jafc.2c05262
|View full text |Cite
|
Sign up to set email alerts
|

Gingerenone A Alleviates Ferroptosis in Secondary Liver Injury in Colitis Mice via Activating Nrf2–Gpx4 Signaling Pathway

Abstract: Patients with ulcerative colitis (UC) have been found to be frequently associated with secondary liver injury (SLI). In this study, we investigated the protective effect of GA on dextran sodium sulfate (DSS)-induced SLI in mice and its mechanism. The SLI was established by adding 4% DSS in the drinking water of mice, and the effects of GA (5, 20 mg/kg, p.o., once a day for 7 days) in hepatic tissues were analyzed. HepG2 cells were induced by lipopolysaccharide (LPS) to detect the effect of GA on ferroptosis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In addition, liver malfunction is a common pathology in obesity and UC. 52,53 We found that the levels of AST and ALT in the serum of obese mice with colitis were higher than those of obese mice alone. Interestingly, G-Rg1, a compound we investigated, has been reported to improve lipid metabolism and liver function.…”
Section: Discussionmentioning
confidence: 84%
“…In addition, liver malfunction is a common pathology in obesity and UC. 52,53 We found that the levels of AST and ALT in the serum of obese mice with colitis were higher than those of obese mice alone. Interestingly, G-Rg1, a compound we investigated, has been reported to improve lipid metabolism and liver function.…”
Section: Discussionmentioning
confidence: 84%
“…59 Additionally, the presence of a leaky gut may exacerbate the secondary liver injury observed in many IBD patients. 60 Notably, several molecules, including monotropein, 61 beta-patchoulene, 62 and gingerenone A, 63 have demonstrated the ability to regulate different signaling pathways and alleviate secondary liver injury induced by colitis, highlighting their potential as treatment options.…”
Section: ■ Discussionmentioning
confidence: 99%
“…By assessing the activity of Fe 2+ , TNF-α, IL-1β, IL-6, GPX4 and Nrf2 , it’s found that Gingerenone A can downregulate Fe 2+ , TNF-α, IL-1β, and IL-6 while upregulating GPX4 expression. The mechanism is Gingerenone A can regulate iron metabolism pathways by activating the Nrf2 /GPX4 pathway, thereby controlling and alleviating ferroptosis in DSS-induced murine UC, ultimately mitigating UC ( Chen et al, 2022 ). High doses of Gingerenone A have a greater therapeutic effect on UC than 5-aminosalicylic acid.…”
Section: The Mechanism Of Tcm Regulating Ferroptosis In the Treatment...mentioning
confidence: 99%
“…Modern pharmacological studies have demonstrated that TCM can prevent and treat UC through various mechanisms, such as reducing oxidative stress, regulating autophagy, and exerting anti-inflammatory effects. Among these mechanisms, TCM targeting ferroptosis has shown significant efficacy ( Chen et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%